Insight into the on/off switch that regulates expression of the MSMEG-3762/63 efflux pump in Mycobacterium smegmatis - Nicoletta Campolattano; Gianluca D’Abrosca; Luigi Russo; Barbara De Siena; Milena Della Gala; Ida De Chiara; Rosangela Marasco; Aaron Goff; Simon J. Waddell; Margherita Sacco; Lidia Muscariello (Scientific Reports, 2023)
Abstract Drug resistance is one of the most difficult challenges facing tuberculosis (TB) control. Drug efflux is among the mechanisms leading to drug resistance. In our previous studies, we partially characterized the ABC-type MSMEG-3762/63 efflux pump in Mycobacterium smegmatis, which shares high percentage of identity with the Mycobacterium tuberculosis Rv1687/86c pump. MSMEG-3762/63 was shown to have extrusion activity for rifampicin and ciprofloxacin, used in first and second-line anti-TB treatments. Moreover, we described the functional role of the TetR-like MSMEG-3765 protein as a repressor of the MSMEG_3762/63/65 operon and orthologous Rv1687/86/85c in M. tuberculosis. Here we show that the operon is upregulated in the macrophage environment, supporting a previous observation of induction triggered by acid-nitrosative stress. Expression of the efflux pump was also induced by sub-inhibitory concentrations of rifampicin or ciprofloxacin. Both these drugs also prevented the binding of the MSMEG-3765 TetR repressor protein to its operator in the MSMEG_3762/63/65 operon. The hypothesis that these two drugs might be responsible for the induction of the efflux pump operon was assessed by bioinformatics analyses. Docking studies using a structural model of the regulator MSMEG-3765 showed that both antibiotics abolished the ability of this transcriptional repressor to recognize the efflux pump operon by interacting with the homodimer at different binding sites within the same binding pocket. Reduced binding of the repressor leads to induction of the efflux pump in M. smegmatis, and reduced efficacy of these two anti-mycobacterial drugs.